Enriching Australian exchange student learning experiences at Japanese universities (Comparative & International Education Series, 2021)
In a world of increasing global connectivity, international engagement is crucial for the survival of the twenty-first century university. As part of a significant strategic push towards further promoting internationalisation, universities in Australia have become increasingly involved in growing the number of students participating in study abroad programs. In the early part of the century, there has been an institutional, strategic alignment toward expanding undergraduate exchange partnerships with overseas universities. Such an alignment allows students to engage in studies at overseas partner universities, as part of their degree program. This growth in exchange study abroad programs has come about with increased recognition of our students’ needs to develop intercultural competencies and awareness, necessary for success in an increasingly globalising workplace. This chapter presents a study that investigates student learning experiences during exchange study abroad from both academic and cultural (dis)engagement perspectives. The aim of the study was to help inform institutional practices to bring about richer exchange study abroad experiences for Australian undergraduate students in Japan. This investigation is of particular importance, as much previous research has explored the study abroad experiences of Asian students studying, predominantly in English-speaking countries. Traditionally, most student mobility has been from non-English speaking countries to English speaking countries. In contrast, our study examines the experiences of English-speaking students going on exchange in Japan - a non-English speaking country - where they must navigate life through both academic (including linguistic) and cultural challenges. True 21st century internationalisation of universities must necessarily be informed by not only inbound but also outbound student learning experiences, thus moving toward more regional equity.The particular focus of our study is on the learning experiences of 20 Australian undergraduate students, from the University of Adelaide, who went on Japan exchange between 2016 and 2018. The study, utilising focus group interviews, investigates how individual students navigated both language and cultural challenges, while studying at Japanese universities. All the students were Japanese Studies majors. To fully capture their experiences, focus group data were collected from the students’ pre-exchange and/or post-exchange reflections. The students studied both Japanese language and Social Science courses (taught in English) at eight different partner Japanese universities: Chuo, Hosei, Kansai, Kansai Gaidai, Nagoya, Okayama, Osaka and Tokyo. In terms of exchange duration, 18 went for one full academic year and 2 for one semester. Participation in the study was voluntary and had ethics clearance. Closed questions were asked to gain demographic information, followed by audio-recorded semi-structured interviews in the focus groups.  Our findings advocate the need for a systematic, equitable institutional approach to consolidating students’ academic readiness and cultural awareness prior to the exchange. Such an equitable approach necessitates balancing institutional responsibilities with individual student’s responsibilities to prepare those students embarking on study abroad in non-English speaking, culturally more distant countries.  Therefore, this chapter offers recommendations for pre-departure good practice, and is of particular interest to those who seek future directions to effectively enhance the study abroad learning experiences of their students in linguistically and culturally non-cognate destinations.